PENGARUH SUBTITUSI TEPUNG IKAN DENGAN TEPUNG CACING TANAH (Lumbricus sp.) TERHADAP PERTUMBUHAN BENUR UDANG WINDU (Penaeus monodon) - Muhammad Ridho Taris; Limin Santoso; Esti Harpeni (University of Lampung, 2018)
Availability of good-quality shrimp feed is an important factor of shrimp increased production. High protein feed can be generated by adding raw materials that contains high protein. One of the raw materials that contains high protein is earthworm meal (Lumbricus sp.). This research goal was to study the influence of the substitution of fish meal by earthworm feed with different proportions toward growth and survival rate of tiger shrimp larvae (Penaeus monodon). The experimental design used Completely Randomized Design (RAL) consists of five treatments with three replications: Feed test A (25% earthworm meal + 75% fish meal), feed test B (50% earthworm meal + 50% fish meal), feed test C (75% earthworms meal + 25% fish meal), feed test D (100% earthworms meal) and feed test E (commercial feed). Results showed that the tiger shrimp which given feed test E is the best result for tiger shrimp growth with 0.480 ± 0.076 grams/individual, while feed test B was the best result for tiger shrimp survival rate with 82 ± 3.46%., and on the feed test D was the best result for tiger shrimp feed conversion rate with 4.0 ± 0.17. Based on results of statistical tests showed that the substitution of fish meal with earthworm meal did not give significant effect on growth and survival rate of tiger shrimp.